PERFORMANCE ANALYSIS OF SOLAR PHOTOVOLTAIC SYSTEMS: A CASE STUDY - Kifayat Ullah Khan,; Nadir Mehran,; Muhammad Abdul Basit Khan, (Spectrum of Engineering Sciences, 2025)
Solar PV technology has become the central pillar of renewable energy strategies all over the world due to its rapid growth rate. The paper offers a thorough analysis of the performance features of solar PV systems by means of an overview of operation data, environmental conditions, and degradation mechanisms. As of 2024, the worldwide capacity of PV is over 1.6 TW, producing 2,136 TWh of electricity per year; it is important to understand the performance of a system in order to maximize energy production and cost-effectiveness. The case study compares various PV installations in various climatic settings and the differences in performance and degradation rates, as well as the environmental influence on the performance of PV systems. Important discoveries are that modern PV systems degrade with an average rate of 0.2-0.8 percent per year, and the environmental conditions known to affect the performance aretemperature, humidity, and dust accumulation on the modules. The research shows that with appropriate monitoring and maintenance, up to 15-25 percent of the efficiency of the system can be enhanced, whereas sophisticated tracking systems can generate up to 30 percent of energy rise. The results help in the design and operation of PV systems to optimize them and promote the global shift towards sustainable energy systems. Keywords Solar photovoltaic, performance analysis, energy efficiency, degradation analysis, renewable energy, system monitoring